Model szkół kształcących nauczycieli jako praktyka partnerstwa pomiędzy uniwersytetami i szkołami kształcącymi nauczycieli i pedagogów: wieloletnie badanie ewaluacyjne w Izraelu - Bar, Nava (Studia Edukacyjne, 2020)
The article presents in its first part the partnership model – PDS (Professional Development School) for teacher education that developed in the 1970s in the United States following criticism and re- search findings that indicated lack of satisfaction with the traditional teacher education programs. In its second part the article presents findings and discussion of a multi-year study conducted over seven years, from 2010 to 2016, in the first and up till now the only PDS partnership incorporated into teacher training program in research university in Israel. The multi-year study focused on stu- dent teachers’ evaluation of the contribution of the teacher training components of the university- school partnership model (PDS) to their learning of teaching: the practice teaching in the school and the school mentors; the groups of student colleagues as learning communities and their weekly meetings and the university coordinators. From the perception of the PDS partnership as a dynamic and developing process and from the approach of evidence-based practice, the importance of this multi year study lies in the identification of the essential strengths in the process of the practical experience expressed in the partnerships for their empowerment. In addition the importance of this research is in the identification of the essential weaknesses and challenges, for the purpose of en- quiry and learning in the learning communities who take part in the PDS partnerships, and the rais- ing of the necessary courses of action and changes. The importance of the research study in the in-ternational aspect lies in the presentation of an additional profile of partnership for the extension of the shared discussion about dilemmas and challenges that arise from the implementation of different partnerships in the training of teachers.